Radioisotopes in Chemical Research: Neutron Activation Analysis of Leaves and Bark of Neem - Garg, A.N.; Verma, Kavita (Asian Journal of Chemistry, 2012)
Radioisotopes are chemical elements with specific mass number that emit characteristic radiation and have definite half-lives. George de von Hevesy was the first to use 210Pb for the determination of solubility of lead salts in water. Neutron activation analysis involves irradiation of the sample with thermal neutrons in a nuclear reactor followed by counting of its g activity by high resolution g-ray spectrometry. Upto 35 elements can be determined by adopting differential counting methodology developed in our laboratory. A non-destructive method has been developed for the determination of phosphorus in biological samples. It involves 5 min irradiation of -100 mg sample in a nuclear reactor, delay by 3 weeks followed by counting of b activity due to 32P using 27 mg/cm2 Al absorber. A large number of medicinal herbs and herbal preparations have been analyzed for minor and trace element contents, which may be attributed to their therapeutic effects. Neem (Azadirachta indica) leaves and bark are widely used for the treatment of a variety of chronic ailments. Analysis of leaves and bark samples collected from different locations exhibit distinctive elemental profile and the contents are indicative of their therapeutic effects.